Conceptual Model of Measuring MHEI Efficiency - Ana Gundić; Dino Županović; Luka Grbić; Mate Baric (MDPI AG, 2020)
Modern societies, new technical equipment and technology confirm the importance of knowledge acquisition in everyday life, especially in economy. An education system is a non-profit system. Since it strongly affects economic efficiency, its quantification becomes a very complex process. In order to make the quantification process possible, this paper analyses the already existing criteria for measuring efficiency in higher education systems. The already existing models of measuring educational efficiency are universal and do not analyse different professions' specific qualities. In this paper, models of measuring educational efficiency were analysed separately, whereas their interrelations were not a part of the analysis. A conceptual model of measuring maritime higher education institutions' (hereinafter: MHEI) efficiency was proposed on the basis of the above-mentioned analysis. All the evaluation criteria relevant for MHEI and their interrelations were determined.